An investigation into the attitude of pupils, teachers and parents towards the educational reforms commencing from 1972 in Sri Lanka - Karunaratne, N.L.D.F. (My University, 1979)
This dissertation is an attempt to investigate the attitudes of pupils, teachers and perents towards the educational reforms effected at the secondary level by the ministry of education in Sri Lanka form 1972. The study endeavoured to find out whether these groups were favourably or unfavourably disposed towars this programme.....